Expression of a chitin deacetylase gene, up‐regulated in Cryptococcus laurentii strain RY1, under nitrogen limitation. (18th January 2016) - Chakraborty, Writachit; Sarkar, Soumyadev; Chakravorty, Somnath; Bhattacharya, Semantee; Bhattacharya, Debanjana; Gachhui, Ratan
Abstract : This study reports the identification of a chitin deacetylase gene in Cryptococcus laurentii strain RY1 over‐expressing under nitrogen limitation by differential display. The up‐regulation took place in robustly growing cells rather than in starving quiescent autophagic cells. Quantitative Real Time‐PCR, enzyme activity in cell lysate and cell wall analysis corroborated the up‐regulation of chitin deacetylase under nitrogen limitation. These results suggest chitin deacetylase might play a significant role in nitrogen limiting growth of Cryptococcus laurentii strain RY1.